Propagation of notch fatigue cracks on maraging steel under biaxial conditions - Cruces, A.S. (2022)
The current work aims at characterizing the fatigue behaviour of an additively manufactured maraging steel. This is a class of highstrength steels widely used in aircracft, aerospace, offshore and military industries thanks to its good performance in terms of strength, toughness, ductility, dimensional stability and weldability. Fabrication of such steel via laser-beam powder bed fusion (additive manufacturing) makes it an excellent candidate for producing prosthetic parts because of its properties, offering a reduction in manufacturing material consumption, labor and machining time. The study is focused on the multiaxial behaviour of the steel, given the wide range of loads often existing in biomedical components. To this end, different critical plane methods are used to predict the fatigue life and the cracking orientation under several biaxial loading scenarios. Thickness effects were also evaluated. Cylindrical specimens were used and these were fabricated in the vertical orientation on the base plate, using a linear printing system equipped with a Nd:YAG fibre laser. The building strategy comprised the deposition of 40 μm thick layers at a scan speed of 80 mm/s. The results are useful to understand the predominant failure mode and the type of critical plane method that is most convenient for such material.